Pengaruh Budaya Organisasi, Pengembangan Karir, dan Komitmen Organisasi Terhadap Kinerja karyawan - Husnul Khatimah; Lutfia Juniarti (Fakultas Ekonomi Universitas Islam 45, 2024)
The purpose of this study was to determine the influence of organizational culture, career development, and organizational commitment on employee performance at the At-Taqwa Narogong Islamic Education Foundation. The research method used in this study is a quantitative method. The population in this study were all employees of the At-Taqwa Narogong Islamic Education Foundation totaling 61 people with a sample of 30 respondents. Using the Statistical Product and Service Solution 26.0 (SPSS) program to analyze data and statistical tests. Based on the results of data processing, it shows that the organizational culture variable has a positive and significant effect on employee performance. The career development variable does not have a positive and significant effect on employee performance. The organizational commitment variable has a positive and significant effect on employee performance. The variables of organizational culture, career development, and organizational commitment together have a positive and significant effect on employee performance.